2000
DOI: 10.1097/00004872-200018050-00004
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of childhood to adult blood pressure

Abstract: Childhood blood pressure is related to adult levels and, together with changes in body mass index, is a significant predictor of adult blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The current study showed that both observed and model-estimated levels of BP during the childhood age period of 4–19 years were significantly, positively associated with adult hypertension in race-gender groups. These observations are consistent with previous longitudinal studies regarding the association between childhood BP levels and adult hypertension (1821,29,30). We also found that model-estimated linear rates of increase in BP during the puberty age period (11–19 years) were significantly and positively associated with the risk of developing hypertension later in life after adjusting for BP levels at these age points.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study showed that both observed and model-estimated levels of BP during the childhood age period of 4–19 years were significantly, positively associated with adult hypertension in race-gender groups. These observations are consistent with previous longitudinal studies regarding the association between childhood BP levels and adult hypertension (1821,29,30). We also found that model-estimated linear rates of increase in BP during the puberty age period (11–19 years) were significantly and positively associated with the risk of developing hypertension later in life after adjusting for BP levels at these age points.…”
Section: Discussionsupporting
confidence: 93%
“…The theory of developmental origins of hypertension is supported by evidence from a large number of longitudinal epidemiological studies showing that childhood BP levels are significantly and positively associated with adult BP levels (1821). Our previous study also demonstrated that BP variability was associated with adult hypertension and BP variability even adjusting for BP levels (22).…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates that adiposity, measured using BMI, has a significant affect on blood pressure tracking from youth to adulthood. Dekkers et al [77] , Klumbiene et al [71] , Lauer et al [78] and Macedo et al [79] had similar findings in relation to BMI change. Yong et al [72] , Macedo et al [79] , Lauer et al [78] and Lambrechtsen et al [80] also demonstrated an association between weight change and blood pressure trajectory change from youth to adulthood.…”
Section: Pathobiological Mechanisms Of Obesity and Elevated Bp In Youthmentioning
confidence: 64%
“…However, both papers included results from tracking studies within youth. Overall, these two reviews and several studies [66][67][68][69][70][71] concluded that the strength of tracking merits population-based prevention aimed at decreasing elevated blood pressure in children, and regular blood pressure screening in an attempt to identify those youth at risk of developing elevated levels in adulthood and whom may benefit from early detection. However, some did not agree with these recommendations [72][73][74] .…”
Section: Tracking Of Blood Pressure From Youth To Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation